High-flow weaning strategies for infants with bronchiolitis: protocol for a pilot randomised controlled trial in the UK - Martin Edwards; Carwyn Dafydd; Christopher Towriss (BMJ Open)
Introduction Ward-based high-flow nasal cannula (HFNC) is an effective therapy for children with bronchiolitis who have failed standard oxygen therapy. However, HFNC can increase hospital length of stay perhaps because there is a lack of evidence to guide weaning strategies.We aim to conduct a pilot study to identify the most effective weaning strategy for infants, up to 12 months, supported on HFNC for bronchiolitis. This may lead to reduced time on respiratory support and shorter length of stay. If this pilot study is deemed feasible, it will inform a larger multicentre trial.Methods and analysis This open label, non-blinded, randomised controlled trial will be conducted over 24 months at the Noah’s Ark Children’s Hospital for Wales, Cardiff, and will aim to recruit 20 patients. It will compare high-flow only weaning (high-flow discontinued at FiO2 of 21%) to HFNC and low-flow weaning (HFNC discontinued at 30% and replaced by low-flow up to 2 L/min). HFNC therapy will be delivered at 2 L/kg/min (maximum 20 L/min). The primary outcome is to examine the feasibility of different weaning strategies for infants with bronchiolitis requiring HFNC. Secondary outcomes include the time from decision to wean HFNC to the patient no longer requiring respiratory support and a safety assessment of the weaning strategies.Ethics and dissemination Health Research Authority and Health and Care Research Wales approval was granted on 8 September 2020 following review by the NHS research ethics committee.The sponsor is Cardiff and Vale University Health Board. We will publish the results in a peer-reviewed medical journal, via websites and newsletters.Trial registration number NCT04287959.